Teachers' general and contextualised research conceptions - Schouteden, Wendy; Verburgh, An; Elen, Jan (Studies in higher education (Dorchester-on-Thames), 2016)
The integration of research into teaching is a new and important focus in teaching-intensive institutions in higher education. Given the paucity of empirical insight into the research-teaching relationship in teaching-intensive institutions, teachers' research conceptions are studied as a first step in understanding the research-teaching relationship. In particular, teachers' general conceptions of what attributes constitute research and the contextualised interpretation of these attributes are studied. Participants were 79 teachers from five teaching-intensive institutions. The study illuminated three categories of general research attributes: research steps, qualities of research processes, and qualities of researchers. From the perspective of their teaching context, teachers reinterpreted the attributes and differentiated between the target of research attributes as well as students' required level of mastery of research attributes.